Diversification, bank performance and risk: have Tunisian banks adopted the new business model? - Helmi Hamdi; Abdelaziz Hakimi; Khemais Zaghdoudi (Financial Innovation, 2017)
Background: The objective of this paper is threefold. First, we test the most important factors that determine the level of non-interest income for Tunisian banks. Second, we study the impact of non-interest income on banks' profitability measured by both return on assets (ROA) and return on equity (ROE). Finally, we investigate the relationship between non-interest income and the level of risk taking. Methods: To achieve this goal, we used annual data of 20 Tunisian banks during the period 2005-2012. In the empirical section we performed a Dynamic Panel Data model. Results: Empirical results indicate that the main determinants of non-interest income are: relative performance (RROA and RROE), bank size, loan specialization and new e-payments channels, automatic teller machine (ATM) and credit cards). We also find that diversification increases bank performance for both ROA and ROE measures. Eventually, non-interest income appears to be negatively and significantly correlated with the effect on the level of risk. Conclusions: Tunisian banks are invited to more diversify their activities and do not focus only on the traditional activity. The noninterest income seems to be associated with a higher level of profitability and a lower risk.
Keywords: 650